TRANSLATING MACHADO DE ASSIS: AN INTERVIEW WITH FLORA THOMSON-DEVEAUX ON THE POSTHUMOUS MEMOIRS OF BRÁS CUBAS AND OTHER DISCOVERIES - Carvalho Fonseca, Luciana; Puello Sydio, Ursula (Revista de Letras, 2021)
Brazilian literature celebrated a milestone in 2020 with two new translations of the novel The Posthumous Memoirs of Brás Cubas by Machado de Assis. One of the translators behind this feat is literary scholar and Brazilianist Flora Thomson-DeVeaux, who granted us this interview with insights on her motivation, translation process, the publishing market, and reception of the translation – the latter exceeding both DeVeaux’s and the publisher’s expectations. Thomson-DeVeaux also shared some of her current and burgeoning projects in Brazil, and how she sees translation and research as forms of "discovery". Keywords: Interview. Translation studies. The Posthumous Memoirs of Brás Cubas. Machado de Assis. Brazilian literature.